RELATIONSHIP BETWEEN INVESTMENT AND COMPETITION LEVEL IN BETWEEN THE POWER OF VARIOUS STATE - Johnson Kennedy, Posma Sariguna (Fakultas Ekonomi Universitas Kristen Indonesia, 2018)
Economic theory and existing empirical studies indicate that higher competition in strategic environments will damage the investment. This study analyzes the relationship between competition and competitor’s interest rate on investment in the country. The data involved five countries, Indonesia and the neighborhood, such as Malaysia, Philippine, Singapore, and Thailand, in twenty years periods evidence, 1989-2008. The competition among countries measured by their relative national capability of investment that approached by their national power weighted by gross saving and balance of payment. While the analysis is shown sensitive to assumption about causality and the numerous problems of pooled data, the result indicate that higher competition has reduced investment in Indonesia and the competitor, about 20%. Another important effect is the existence of small positive impact of the competitor’s riil interest rate on investment in Indonesia, about 0,05% although not significant. In this study also found the different evidence that higher riil interest rate by competitor country, Singapore, do not promote the investment in Indonesia. This happened may caused of capital flight from Indonesia to the nearest country, Singapore, for investing in their higher interest rate.Keywords : Investment, International Investment. Klasifikasi JEL : F21